Post-mortem Characterisation of a Case With an ACTG1 Variant, Agenesis of the Corpus Callosum and Neuronal Heterotopia - Vontell, Regina; Supramaniam, Veena G.; Davidson, Alice; Thornton, Claire; Marnerides, Andreas; Holder-Espinasse, Muriel; Lillis, Suzanne; Yau, Shu; Jansson, Mattias; Hagberg, Henrik E.; Rutherford, Mary A. (Frontiers in Physiology, 2019)
Cytoplasmic Actin Gamma 1 (ACTG1) gene variant are autosomal dominant and can cause CNS anomalies (Baraitser Winter Malformation Syndrome; BWMS). ACTG1 anomalies in offspring include agenesis of the corpus callosum (ACC) and neuronal heterotopia which are ectopic nodules of nerve cells that failed to migrate appropriately. Subcortical and periventricular neuronal heterotopia have been described previously in association with ACC. In this case report, we investigated a neonatal brain with an ACTG1 gene variant and a phenotype of ACC, and neuronal heterotopia (ACC-H) which was diagnosed on antenatal MR imaging and was consistent with band heterotopia seen on post-mortem brain images. Histologically clusters of neurons were seen in both the subcortical and periventricular white matter (PVWM) brain region that coincided with impaired abnormalities in glial formation. Immunohistochemistry was performed on paraffin-embedded brain tissue blocks from this case with ACTG1 variant and an age-matched control. Using tissue sections from the frontal lobe, we examined the distribution of neuronal cells (HuC/HuD, calretinin, and parvalbumin), growth cone (drebrin), and synaptic proteins (synaptophysin and SNAP-25). Additionally, we investigated how the ACTG1 variant altered astroglia (nestin, GFAP, vimentin); oligodendroglia (OLIG2) and microglia (Iba-1) in the corpus callosum, cortex, caudal ganglionic eminence, and PVWM. As predicted in the ACTG1 variant case, we found a lack of midline radial glia and glutamatergic fibers. We also found disturbances in the cortical region, in glial cells and a lack of extracellular matrix components in the ACTG1 variant. The caudal ganglionic eminence and the PVWM regions in the ACTG1 variant lacked several cellular components that were identified in a control case. Within the neuronal heterotopia, we found evidence of glutamatergic and GABAergic neurons with apparent synaptic connections. The data presented from this case study with BWMS with variants in the ACTG1 gene provides insight as to the composition of neuronal heterotopia, and how disturbances of important migratory signals may dramatically affect ongoing brain development.